Antitumor evaluation of hydroxyurea analogue Schiff base metal complexes - Telceken, Hafize; Karatepe, Arzu; Çeribaşı, Songül; Genç, Zuhal Karagöz; Çeribaşı, Ali Osman (University of Benin, 2024)
Purpose: The in vivo and in vitro antitumor activities of hydroxyurea derivative Schiff bases (SBs) metal complexes were investigated in immortalized human colon cancer cell lines (HT-29 cells) and rat models.Methods: For the in vitro studies, three concentrations (5, 10, and 20 ?M) of the 1-hydroxy-3-(E)- pyridine-3-ylmethylidene urea derivative SB (L)-metal complexes (L-Cd, L-Cu, L-Zn) were used to determine the viability of HT-29 cell line with dimethylsulphoxide (DMSO) as control. On the other hand, colorectal cancer was induced with subcutaneous administration of azoxymethane (AOM; 15 mg/kg) in 35 Wistar albino rats, which were assigned to five treatment groups consisting of DMSO (negative control), cisplatin (15 mg/kg, positive control), AOM + L-Cd (25 mg/kg), AOM + L-Cu (25 mg/kg) and AOM + L-Zn (25 mg/kg) groups, respectively. Tumor formation was observed by macroscopic and microscopic examinations.Results: Tumour formation was not observed in the positive control group. The rats treated with AOM (excluding L-Cu and cisplatin group) displayed severe dysplasia and adenocarcinoma formations in the oil+DMSO, L-Cd and L-Zn groups. When compared with the cisplatin group in the in vivo studies, the Cu complex had a more favorable effect against colon cancer.Conclusion: Consequently, hydroxyurea derivative SB-metal complexes exhibit antiproliferative activity in both in vitro (p < 0.0001) and in vivo studies. © 2024 The authors.
Keywords: Antiproliferative; Azoxymethane; Colon cancer; Hydroxyurea; Schiff base